Do Some Sustainability Reporting Measures Enable Esg Greenwashing: A Case Study Of Oil And Gas Industry In Malaysia - Nurul Nazlia Jamil; Ersa Tri Wahyuni (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA